The Explorer's Eye : First-Hand Accounts of Adventure and Exploration - Edited by Fleming, Fergus and Merullo, Annabel (London Ted Smart, 2005)
In the 18th century, exploration entered a new dimension - explorers were motivated by scientific inquiry rather than greed. To this end they were expected to make a full record of everything they encountered; and for the first time in history, that record was to include pictures as well as words. Combining gripping first-hand accounts with original images, "The Explorer's Eye" gives an insight into who these people were and what they saw. They were a mixed bunch but, whatever their training or background, they provided a vivid portrait of the unknown. In the early days they drew their own pictures, later they were equipped with draughtsmen, later still they carried cameras, and ultimately they were accompanied by film crews. The power of their images is matched by that of their journals. Here you have Alexander von Humboldt braving the electric eels of South America, Robert Peary explaining his relationships with Eskimos, Jacques Cousteau examining the planet from under the waves and Neil Armstrong doing the same from outer space
Include Color Illustration and Index
Keywords: Voyages and travels -- Discoveries in geography -- Explorers